Deathwatch : American film, technology, and the end of life - Combs, C. Scott (New York : Columbia University Press, 2014)
While cinema is a medium with a unique ability to 'watch life' and 'write movement, ' it is equally singular in its portrayal of death. This book considers movie sequences in which the process of dying becomes an exercise in legibility and exploration for the camera and connects the slow or static process of dying to formal film innovation throughout the 20th century.
Acknowledgments -- Introduction: An Elusive Passage -- 1. Mortal Recoil: Early American Execution Scenes and the Electric Chair -- 2. Posthumous Motion: The Deathwork of Narrative Editing -- 3. Echo and Hum: Death's Acoustic Space in the Early Sound Film -- 4. Seconds: The Flashback Loop and the Posthumous Voice -- 5. Terminal Screens: Cinematography and Electric Death -- Coda: End(Ings) -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Death in motion pictures; Mortality in motion pictures; Motion pictures -- United States -- History and criticism; Mort au cinéma.; Mortalité au cinéma.; Cinéma -- États-Unis -- Histoire et critique; PERFORMING ARTS -- Reference; PHILOSOPHY -- Aesthetics; Death in motion pictures; Mortality in motion pictures; Motion pictures; United States; Electronic books; Criticism, interpretation, etc